THE MESSAPIC ELEMENT -IHI: A NEW INTERPRETATION - Kujtim Mani (Alfred Nobel University Journal of Philology)
The lexical item -ihi~aihi in Messapic epigraphy poses a significant challenge for scholars, functioning as a vital grammatical and semantic component in inscriptions. This article seeks to reassess the role of -ihi, suggesting it may function as an interjection or a reflection of -i rather than merely as a genitive marker. By offering a reinterpretation of -ihi, the study aims to establish a new framework for the fragmentation, analysis, and interpretation of Messapic inscriptions. This fresh perspective will be explored through detailed examination of selected examples, incorporating internal-comparative analysis, methods of ‘frame semantics’ (according to Ch.K. Fillmor and S. Marchesi- ni), linguistic anthropology, and the hermeneutic method. Initially identified in the 19th century as a genitive ending, -ihi has garnered significant scholarly at- tention as a pivotal element in text fragmentation, serving both as a marker and a guiding principle thereof. However, persistent debates have arisen regarding its exclusive function as a genitive marker, with some scholars contending that it solely denotes nouns, adjectives, and pronouns. This dichotomy has posed chal- lenges in conceptualizing word fragmentation beyond the grammatical function of -ihi, fostering a geni- tive-centric perspective that has rendered Messapic somewhat enigmatic, even labeled as a ‘phantom lan- guage’. The assertion that the majority of Messapic vocabulary consists of nouns ending in -ihi has intensi- fied scholarly interest, prompting deeper investigations into its nature. Yet, despite its declared function as genitive, exploring alternative roles for this lexical item, particularly in the context of potential Illyrian or Proto-Albanian origins, remains largely unexplored territory. Considering the conceivable historical inter- play of -ihi~aihi within the context of Illyrian – Proto-Albanian > Classical Albanian, an etymological explo- ration seems justified, especially from an internal-comparative perspective. An examination of the classical Albanian tradition, which predominantly employs the suffix -h at the end of words terminating with vowels, such as in the case of Buzuku (1555), suggests a possible connection between -hi and this suffix, perhaps as a post-vocalic resonance rather than solely a genitive marker. Fur- thermore, parallels between Messapic genitive structures and Proto-Albanian remnants, which persisted into the post-Messapic era and even into modern Albanian, hint at a broader linguistic continuity. While -ihi undoubtedly aids in text segmentation, serving both as a word ending and occasionally as an emotional interjection, its classification solely as a genitive marker oversimplifies its linguistic signif- icance. Examples highlighting the interpretive paradoxes surrounding -ihi underscore the need for a nu- anced examination of its multifaceted roles, including its potential as a reflection of the -i ending or an in- terjection mimicking mourning practices, particularly in funerary contexts. The efficacy of -ihi in formal text segmentation notwithstanding, the question of its true linguistic function persists: is it primarily a genitive ending, a reflection of the -i ending, or an interjection? This inqui- ry demands thorough investigation, especially considering its implications for understanding Messapic lan- guage and culture. By delving into these complexities, this article aims to illuminate the enigmatic nature of -ihi and its broader significance in the study of Messapic epigraphy and Albanian linguistic evolution.